USE OF MULTIMEDIA TECHNOLOGIES IN TEACHING A FOREIGNLANGUAGE - Karshiyeva, Ruzigul (Журнал иностранных языков и лингвистики, 2023)
This paper examines the basic stages of teaching foreign languages and their psychological and linguistic analysis. Features of linguistic material predetermine the specificity of work on its assimilation. Characterized by a process of assimilation of linguistic material in certain periods.